Indonesian Pre-service and In-service Science Teachers’ TPACK Level - Emayulia Sastria (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This current study aimed to examine the levels of TPACK among pre-service and in-service science teachers, including several influencing factors such as gender, status, and age. Through a study of TPACK dimensions of the 211 pre-service and in-service biology teachers and science teachers were identified. The results depicted that pre-service and in-service science teachers dominate the understanding and application of non-technological dimensions. Otherwise, it was found that technological dimensions needed to be more knowledgeable for pre-service and in-service science teachers. The analysis of the variance test demonstrates significant differences were identified regarding status and age. However, no dimension was found to be significantly different regarding age level. To sum up, pre-service and in-service science teachers have different understandings and applications of ICT integration in science classrooms. Professional teaching can be developed by improving knowledge and skills of technology, pedagogy, content, and their integration.